Hybrid liquid crystals tetrazolyl and isoxazolyl cinnamates. Issue 11 (1st September 2016) - da Rosa, Rafaela R.; Tariq, Muhammad; Weber, Caroline S. B.; Hameed, Shahid; Silva, Sidnei; Merlo, Aloir A.
ABSTRACT: In this work, a series of isoxazolyl and tetrazolylcinnamic ester hybrid liquid crystals (HLCs) were synthesised and their mesomorphic behaviour was analysed. Cinnamic acid derivatives were prepared by Knoevenagel condensation of malonic acid and arylaldehydes. Five-membered tetrazoles and isoxazoles were prepared by [3 + 2] 1, 3-dipolar cycloaddition. Tetrazoles were synthesised by sodium azide addition to arylnitrile, while isoxazoles were synthetised by arylnitrile oxide addition to alkenes to form isoxazolines, followed by MnO2 -oxidation. Tetrazolyltolane compounds were also synthesised and their LC behaviour compared with cinnamic esters. HLCs containing isoxazole rings displayed a large mesophase range with high clearing temperature ( T c ), with predominance of smectic mesophases SmA and SmC. The HLCs decomposed upon heating due to their high clearing temperature (>250°C). HLCs with tetrazole rings showed a narrow nematic mesophase range with enantiotropic or monotropic behaviour. GRAPHICAL ABSTRACT: